Bridging Local Concerns and Systemic Change: A Design-Based Approach to Transformative Climate Education - Houlden, Shandell; Lange, Elizabeth (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
This article presents the initial research and development phases of a transformative climate education program for adults in a semi-rural community on southern Vancouver Island. Using design-based research (DBR), we developed a workshop series informed by adult and lifelong education (ALE), transformative learning, and the theoretical frameworks of the Gesturing Towards Decolonial Futures Collective and its members, including Vanessa Machado de Oliveira. Our research began with a community needs assessment (n = 183), identifying key concerns such as affordability, climate anxiety, and social cohesion. We articulate six design principles emerging from these insights, which highlight the importance of pedagogical entry points, the role of worldview transformation, and the integration of localized climate solutions with broader systemic critiques. This study contributes to climate education by offering a model that moves beyond information dissemination, and instead cultivates critical, justice-oriented engagement with climate action in ways that are both locally relevant and globally situated.